2023
DOI: 10.1161/cir.0000000000001162
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making and Cardiovascular Health: A Scientific Statement From the American Heart Association

Abstract: Shared decision-making is increasingly embraced in health care and recommended in cardiovascular guidelines. Patient involvement in health care decisions, patient-clinician communication, and models of patient-centered care are critical to improve health outcomes and to promote equity, but formal models and evaluation in cardiovascular care are nascent. Shared decision-making promotes equity by involving clinicians and patients, sharing the best available evidence, and recognizing the needs, values, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 128 publications
(214 reference statements)
0
14
0
Order By: Relevance
“…Studies were included in this review if they met the following criteria: (1) the population included adults (aged Ն18 years) with cardiovascular risk factors (diabetes, hypertension, dyslipidemia, overweight and obesity, and tobacco use); (2) an SDM-based intervention type was used; (3) outcomes examined included decisional outcomes (decisional conflict, decisional quality, or SDM scores), cardiovascular risk factor outcomes (HbA 1c , SBP levels, low-density lipoprotein, total cholesterol, smoking cessation, or CVD risk), and health behavioral outcomes (physical activity, healthy diet, or medication management); and (4) a randomized clinical trial (RCT) study design was used. In our systematic review, we identified interventions as SDM based if they met the following criteria based on the published scientific statement 5 : clinicians and patients made decisions together, the best available evidence was used, and decisions were based on patients' informed values or preferences.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were included in this review if they met the following criteria: (1) the population included adults (aged Ն18 years) with cardiovascular risk factors (diabetes, hypertension, dyslipidemia, overweight and obesity, and tobacco use); (2) an SDM-based intervention type was used; (3) outcomes examined included decisional outcomes (decisional conflict, decisional quality, or SDM scores), cardiovascular risk factor outcomes (HbA 1c , SBP levels, low-density lipoprotein, total cholesterol, smoking cessation, or CVD risk), and health behavioral outcomes (physical activity, healthy diet, or medication management); and (4) a randomized clinical trial (RCT) study design was used. In our systematic review, we identified interventions as SDM based if they met the following criteria based on the published scientific statement 5 : clinicians and patients made decisions together, the best available evidence was used, and decisions were based on patients' informed values or preferences.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…4 This approach enables patients, in concert with their clinicians, to make informed decisions about their health care that incorporate their goals, values, and preferences. 5 Previous systematic reviews showed that the implementation of SDM in primary care may be effective in reducing decisional conflict and improving knowledge of diseases and treatment options, awareness of risk, and satisfaction with the decisions made. [6][7][8][9] The incorporation of SDM in cardiovascular risk prevention and management has the potential to increase patient engagement in lifestyle changes, medication adherence, and glycemic and blood pressure control and lead to improved health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important aspect is considering patient autonomy and developing shared decision-making approaches to increase patient participation in their care, hence making the programme more effective. Interventions exist, such as educating the healthcare team on communication techniques; engaging multidisciplinary approaches, including decision coaches; and using patient decision aids, appropriate for the literacy and numeracy levels of the patient populations 12. Different preferences for treatment might require a careful balancing of patient preferences and best effectiveness aimed with the HEARTS approach, for example, when considering stepwise treatments to reach hypertension control.…”
Section: What Are the Challenges?mentioning
confidence: 99%